Bridging Local Wisdom and Digital Literacy: Development of an Interactive Nearpod Assessment for Junior High School - Sri Wahyuni; Sitti Widatul Hasanah; Arvidhea Safira Gunawan; Eka Puspita Kartika Sari; Himatus Sya'adah (Yayasan Keluarga Guru Mandiri, 2026)
One of the 21st-century competencies is digital literacy. However, science assessment in junior high schools is less integrated with digital literacy and contextual content. Few studies examine integrating literacy assessment tools with local wisdom and interactive platforms, such as Nearpod. This gap highlights the need for innovative, context-based digital assessment tools. This research aims to develop a digital literacy assessment tool in Nearpod using coconut shell processing on the topic of substances and their transformations. It used a Research and Development (RD) model modified from the Borg and Gall model, with eight phases: needs analysis, planning, instrument design, expert validation, initial revision, small-scale testing, product revision, and large-scale field testing. The tool included a series of multiple-choice items in an interactive Nearpod format. Findings show very high validity. Out of 50 items, 20 of them were valid in the small-scale test and were all valid in the large-scale test. Items were well discriminated and of equal difficulty. By combining locally relevant content with Nearpod-based assessments, this research highlights a previously underexplored area in science assessment, resulting in a culturally meaningful and digitally engaging instrument for junior high school students.